COVID-19 infection among healthcare workers in an oncology hospital - İskender, Gülşen; Mert, Duygu; Avşar, Zühal; Kölgelier, Servet; Ertek, Mustafa (The Journal of Infection in Developing Countries, 2023)
Introduction: Healthcare workers are at high risk for acquiring COVID-19 and transmitting it to the patients especially to cancer patients in whom the risk of severe COVID-19 is high. We determined the rate of COVID-19 infection among healthcare workers in an oncology hospital and their epidemiological characteristics. Methodology: Data of infected workers from March 11, 2020, to February 28, 2022 were obtained via Infection Control Committee COVID-19 Surveillance Records and evaluated retrospectively. Results: During this period 58.34% of 2,355 workers were vaccinated with > 3 doses of COVID-19 vaccines. A total of 1,294 COVID-19 attacks developed in 1,181 (50.14%) workers; mean age was 38.08 ± 9.52 years, 744 (63%) were female. Re-infection occurred in 112 (9.5%) workers. Source of infection in 858 attacks (66.31%) was unknown. Hospitalization was needed in 24 (2%) and intensive care unit admission in 1 (0.08%), no death occurred. In the first attacks, 587 (49.70%) were unvaccinated; in re-infections 66 (58.92%) were ≥ 3 doses vaccinated. Hospitalizations were predominantly in the pre-Delta period (16/24: 66.7%, p < 0.05). Re-infections occurred mostly in the Omicron variant period (p < 0.05). Relationship between hospitalization and male gender, age ≥ 50 years, "doctor" profession and presence of chronic diseases were significant (p < 0.05). Conclusions: During the study period, half of the healthcare workers in our hospital developed COVID-19 infection of whom 9.5% re-infected, predominantly during the Omicron variant period. Our findings highlight the importance of taking preventive measures and administering booster vaccine doses even after initial vaccination/infection.